Development of Face Recognition Smart Door Lock System Using ESP32-CAM and Telegram Application As Media Control and Monitoring - Binti Harun, Nurhamirah; Bin Zainal, Mohd Shamian (Progress in Engineering Application and Technology, 2023)
Face recognition system is widely used for human identification. It is because of the ability to measure and subsequently identify humans, mainly for security purposes (H. Hassan, R. A. Bakar and A. T. F. Mokhtar). It can be used as a security system at home to prevent robbers from entering the house. This paper presents the development of an IoT-based door lock system that recognizes a   face to unlock a door lock. This project consists of several pieces of hardware, such as an ESP32 Cam that acts as a microcontroller that carries input and output to switch on/off the magnetic lock, a smartphone, and other hardware components listed later in this paper. ESP 32 Cam will receive a signal and unlock the door if the user is recognized. Otherwise, the alert system will notify Telegram Application with a buzzer addition. One of the main functions of a smart door lock system is saving energy consumption to lock and unlock the door and make daily human tasks easier. The time needed to operate the appliances can be reduced by using the face recognition system, and it helps people with disability to control the devices more efficiently. This project is designed with a great security system that uses portable hardware, is high efficiency, low cost, and is easy to operate. In this project, the smartphone receives notifications and can be controlled manually using the Telegram system. The appliances can be controlled and monitored easily through the Internet or Wi-Fi, linked to the smartphone's Telegram Application. This controlling system can be suitable for the lifestyle of people, and they can activate the method according to their preferences. For a future project, improvement can be made by adding a directional antenna to increase the Wi-Fi range. The ESP32-CAM can upgrade to the latest version on the market or change to a new version of Raspberry Pi, which is more powerful and has more features and security.